2022
DOI: 10.1007/s11356-021-17444-z
|View full text |Cite
|
Sign up to set email alerts
|

Local fruit wastes driven benthic microbial fuel cell: a sustainable approach to toxic metal removal and bioelectricity generation

Abstract: The present work focused on the utilization of three local wastes i.e., rambutan (nephelium lappaceum), langsat (lansium parasiticum) and mango (mangifera indica) wastes as organic substrates in benthic microbial fuel cell (BMFC) to reduce the cadmium and lead concentrations from synthetic wastewater. Out of the three wastes, the mango waste promoted a maximum current density (87.71 mA/m 2 ) along with 78 % and 80 % removal efficiencies for Cd 2+ and Pb 2+ , respectively. The bacterial identification proved th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 65 publications
(47 reference statements)
0
18
0
2
Order By: Relevance
“…According to prior research, soluble metal ions in MFCs become insoluble (sludge form) after the MFCs’ operation. In our previous work, the MFC mechanisms (electron generation and transportation) are well explained [ 20 , 52 , 53 ]. Furthermore, the reduction process occurred when the electrons were effectively delivered to the cathode through the outside circuit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to prior research, soluble metal ions in MFCs become insoluble (sludge form) after the MFCs’ operation. In our previous work, the MFC mechanisms (electron generation and transportation) are well explained [ 20 , 52 , 53 ]. Furthermore, the reduction process occurred when the electrons were effectively delivered to the cathode through the outside circuit.…”
Section: Resultsmentioning
confidence: 99%
“… Mechanism of MFCs in the generation of electrons and the reduction of metal ions (Reproduced from reference [ 53 , 55 ] with Elsevier and Springer nature permission). …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…In this context, it is worth mentioning that in microbial fuel cells, the transfer of electrons from microorganisms to the electrode is produced by various mechanisms, including through pili or nanowires after the formation of a biofilm on the electrode [ 62 , 63 ]. It has been reported that this species exhibits a direct transfer of electrons without the help of mediators, using glucose as a carbon source, and that this yeast also has redox enzymes present in the cell membrane of the cell, which contribute to the production of current in an MFC [ 64 , 65 ]. Finally, Figure 6 shows the bioelectricity generation mechanism of using pineapple waste as fuel in single-chamber microbial fuel cells, where it is observed that the three fuel cells connected in series were capable of generating 2.85 V, which was enough to turn on an LED bulb (white) on the fifteenth day.…”
Section: Results and Analysismentioning
confidence: 99%
“…As a result, it is crucial to develop a coarse-grained protocol that balances the accuracy and efficiency of modeling AEM. With careful model construction and force field parameterization, CG simulation can also be applied to studying other ion-conductive polymers [ 52 ] or novel materials for microbial fuel cells [ 50 , 53 ].…”
Section: Introductionmentioning
confidence: 99%